Aplicação web para criação de mapas temáticos em agricultura de precisão - Borges, Ligia Francielle (2017)
The analysis of thematic maps, in the precision agriculture (AP) context, is a resource used to understand the spatial variability of soil attributes in cultivated areas, witch can bring important subsidies for rational handling, improving yield and reducing environmental impact. Thus, the main goal of this research was to develop and make available a web-based software, which provides the ability to draw thematic maps according to well-known methods of data interpolation (inverse of distance weighted, moving average, nearest-neighbor). The software was tested with AP research data (physical and chemical soil attributes and corn yield) developed in a 19.8 ha agricultural area located in the western region of Parana state. The use of the software made possible generating thematic maps of variables usually used in precision agriculture, allowing to evaluate the distribution of each attribute in the area and identify possible causes of variations in yield. As the software is installed in a on-demand server, it provides good performance from a functional point of view and can be accessed from any web environment (browser).